Promoting fruit tree cultivation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Lesoga Motoma, Executive Director of the Forestry Association of Botswana explains how her organisation is promoting fruit tree cultivation.